2012
DOI: 10.1186/1752-153x-6-43
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of flavonoids contents and in vitro antioxidant activity of Launaea procumbens

Abstract: BackgroundLaunaea procumbens (LP) has been used as a food supplement in Pakistan. In this study methanolic crude extract (LPME) of the whole plant and its different fractions; n-hexane (LPHE); ethyl acetate (LPEE) and chloroform (LPCE) were studied for the determination of total flavonoid and phenolics contents along with multifaceted in vitro scavenging assays.ResultsConsiderable amount of flavonoid and phenolics contents were found in all the fractions. Methanol and chloroform fraction exhibited efficient sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(111 citation statements)
references
References 49 publications
11
100
0
Order By: Relevance
“…In both leaf extracts, there was a dose-dependent increase in total antioxidant activity. Many flavonoids and related polyphenols contribute significantly to the phosphomolybdate scavenging activity of medicinal plants [52,53]. The present study was in agreement with the above findings and indicated that the presence of significant levels of non-enzymic antioxidants, namely, flavonoids and polyphenols in leaf extracts of Alternanthera plants might contribute to the phosphomolybdate scavenging activity which was measured as TAC.…”
Section: Tacsupporting
confidence: 80%
“…In both leaf extracts, there was a dose-dependent increase in total antioxidant activity. Many flavonoids and related polyphenols contribute significantly to the phosphomolybdate scavenging activity of medicinal plants [52,53]. The present study was in agreement with the above findings and indicated that the presence of significant levels of non-enzymic antioxidants, namely, flavonoids and polyphenols in leaf extracts of Alternanthera plants might contribute to the phosphomolybdate scavenging activity which was measured as TAC.…”
Section: Tacsupporting
confidence: 80%
“…Flavonoids are the chief of phenolic compounds and they also have potent antioxidant activities with positive effects on human health [33]. The total flavonoid content in leaves of Q. salicina and Q. serrata were much higher than that of Launaea procumbens which as a food supplement in Pakistan (4 -13 mg RE/g DW) [34]. From the results, this study concluded that leaves of Q. salicina and bark of Q. serrata may obtain rich phenolics and should be further elaborated to exploit their biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant capacity of the fractions was measured spectrophotometrically through phosphomolybdenum method, based on the reduction of Mo (VI) to Mo (V) by the test sample and the consequent formation of green phosphate/Mo (V) compounds. Recent studies have shown that numerous flavonoid and related polyphenols contribute significantly to the phosphomolybdate scavenging activity of medicinal plants (Sharififar et al, 2009;Khan et al, 2012). Regarding the result of total antioxidant activity, the methanol and chloroform fractions of R. dumetorum contain antioxidant compounds as equivalents of ascorbic acid to efficiently decrease the oxidant in the reaction matrix.…”
Section: Discussionmentioning
confidence: 99%